2017
DOI: 10.1016/j.jcrc.2017.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic changes with paracetamol in critically-ill children

Abstract: Purpose: Paracetamol has been associated with a reduction in blood pressure, especially in febrile, critically-ill adults. We hypothesised that blood pressure would fall following administration of paracetamol in critically-ill children and this effect would be greater during fever and among children with a high body surface area to weight ratio. Methods:A 12-month prospective observational study of children (0-16 years) admitted to paediatric intensive care, who underwent pulse contour analysis and received p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…Similarly, a study in children after cardiac surgery found that 1 in every 20 administrations of paracetamol (5%) was associated with a 15% drop in MAP from baseline [13]. However, this study, like the previous one [12], evaluated the change in MAP, not true hypotension.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Similarly, a study in children after cardiac surgery found that 1 in every 20 administrations of paracetamol (5%) was associated with a 15% drop in MAP from baseline [13]. However, this study, like the previous one [12], evaluated the change in MAP, not true hypotension.…”
Section: Introductionmentioning
confidence: 80%
“…Ray et al [12] reported a mean decrease of 4.8% (3.3 mmHg) in MAP from baseline (68 mmHg) in critically ill children. However, they included all routes of paracetamol administration, which may affect drug delivery and MAP change, and the reported decrease in MAP per se, which does not indicate true hypotension.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A key mechanism for lowering temperature is by initiation of cutaneous vasodilation, [50][51][52] similar to what occurs during defervescence, which facilitates arterial heat dissipation from the skin. This vasodilation can occur to varying degrees in a febrile patient, but studies in both adults [53][54][55] and children 56,57 have shown this often leads to a clinically significant fall in mean arterial pressure. The subsequent acetaminophen-induced hypotension is then countered with fluid and/or vasopressor support to maintain adequate organ perfusion.…”
Section: Fluidmentioning
confidence: 99%
“…The subsequent acetaminophen-induced hypotension is then countered with fluid and/or vasopressor support to maintain adequate organ perfusion. [53][54][55][56][57] Thus, a vicious cycle ensues as we desperately work against the normal physiology of the body to maintain blood pressure, but as total body water stores increase, oxygenation in the lungs then becomes compromised, inducing unnecessary harm. 58 The time for an evidence-based approach to fluid management in the febrile patient is long overdue.…”
Section: Fluidmentioning
confidence: 99%